Pendampingan Guru PAUD dalam Mengintegrasikan Computational Thinking melalui Aktivitas Unplugged pada Pembelajaran Anak Usia Dini - Popi Dayurni; Kurniati Rahmadani; Ade Fricticarani; Siti Aspariah; Nur Hidayanti; Babay Suhendri (Gema Cendekia Institute, 2026)
The rapid development of digital society demands the strengthening of 21st-century skills from an early age, including computational thinking (CT). However, the integration of CT in early childhood education remains limited, particularly due to teachers’ lack of conceptual understanding and pedagogical strategies. This community service program aimed to assist early childhood teachers, members of HIMPAUDI, in integrating computational thinking through unplugged activities using a Participatory Action Research (PAR) approach. The program involved 16 teachers and was conducted through collaborative stages, including problem identification, joint action planning, workshop implementation, simulation, reflection, and evaluation. The results indicate a significant improvement in teachers’ understanding of CT concepts, their ability to design unplugged activities, and their confidence in classroom implementation. The participatory process enabled teachers to recognize that computational thinking can be embedded in play-based learning through structured activities such as sequencing, pattern recognition, and algorithmic instruction. Beyond individual competency enhancement, the program also fostered the formation of a community of practice and the emergence of local leaders within the teacher group, indicating early signs of social transformation. Theoretically, the findings reinforce the perspective that computational thinking is not limited to digital programming but represents a systematic way of thinking that can be developed through concrete and contextual learning experiences. The PAR approach proved effective in promoting sustainable pedagogical change by positioning teachers as active agents of transformation. This program demonstrates that integrating CT through unplugged activities is a feasible, inclusive, and sustainable strategy for strengthening early childhood education in the 21st century.